PENERAPAN METODE IMPROVED EXPONENTIAL APPROACH DALAM MENYELESAIKAN MASALAH TRANSPORTASI FUZZY DI PERUM BULOG SUB.DIVRE MEDAN - Tika Pratiwi; Zahedi Zahedi (LPPM Universitas Bina Bangsa, 2022)
Transportation is an activities that affect the smooth wheels of the economy. The core problem of transportation is to minimize distribution costs. Matters that affect distribution costs are in the form of demand quantities, supply quantities, and transportation costs. In 2021, the rice distribution costs of Perum Bulog Sub Divre Medan was very high accompanied by uncertain demand and supply so it is expressed in fuzzy numbers. It is necessary to use a method that can solve this transportation problem optimally. In this study, the improved exponential approach method was used to find the optimal solution in rice distribution and combined with fuzzy integer transportation to find the integer value of the parameters with fuzzy values. The improved exponential approach method is a method of solving balanced and unbalanced transportation problems directly. The results showed that the improved exponential approach method can be applied to solve the fuzzy transportation problem. The cost of distributing rice in 2021 using the improved exponential approach method has decreased by IDR 41,155,480 from the actual distribution cost. Through these results, it can be concluded that the improved exponential approach method can optimally solve the fuzzy transportation problem in 2021 at Bulog Sub-Divre Perum Medan